Dyadic effects of minority stress and problematic alcohol use on sexual intimate partner violence in same sex couples. Issue 3 (24th January 2023) - Parrott, Dominic J.; Bresin, Konrad; Hequembourg, Amy; Velia, Brynne; Swartout, Kevin M.; Stappenbeck, Cynthia A.; Masyn, Katherine E.; Grom, Jessica L.
Abstract: Little is known about the factors that facilitate the perpetration of sexual violence within the context of same‐sex romantic relationships (sexual intimate partner violence perpetration [S‐IPV]). The present study sought to identify the effects of external and internal minority stress and problematic drinking on perpetration of S‐IPV within a dyadic framework. A community‐based sample of 137 sexual and gender minority (SGM) couples ( N = 274; 59 male assigned at birth and 78 female assigned at birth couples) completed self‐report surveys about minority stressors, alcohol use, and S‐IPV perpetration. Multilevel logistic regression analyses were conducted within an actor‐partner interdependence framework. This approach accounted for both actor effects (e.g., how much one's S‐IPV perpetration is predicted by their own risk factors) and partner effects (e.g., how much one's S‐IPV perpetration is influenced by their partner's risk factors). Both Actor external minority stress and internal minority stress were positively associated with Actor S‐IPV perpetration. Actor problematic drinking was not associated with Actor S‐IPV perpetration; however, Partner problematic drinking was positively associated with Actor S‐IPV perpetration. Observed effects were robust above the addition of other risk factors. This research innovatively extricates S‐IPV perpetration from other forms of IPV and indicates that Actor minority stress and Partner problematic drinking increase S‐IPV likelihood. Results serve as a starting point for development of etiological models to inform the design of culturally‐informed interventions to reduce S‐IPV among SGM couples.